Same same but different: how preferential claims trigger valuation discounts in equity tranches of VC-backed firms - Julian Kaboth; Arnd Lodowicks; Maximilian Schreiter; Bernhard Schwetzler (Review of Quantitative Finance and Accounting, 2022)
Venture capital (VC) often involves complex equity contracts with so-called preferential rights affecting the allocation of exit proceeds among different share classes and investors. We structure exit-relevant preferential rights in a two-dimensional framework and develop a contingent claims model that allows for ex-ante valuation of separate shareholdings. The model generates insights on the valuation effects of varying setups in VC financing and indicates considerable mispricing potential of VC investments when applying commonly used heuristics such as the most recent funding round. Applying the model to a sample of ventures indicated an average 'overvaluation' on a per-share basis of 26.7%, with common stocks and early-stage investments being the most affected. In addition, our analysis provides different implications regarding the effects of preferential right structuring for early and late stage investors.
Keywords: M13; G12; G13; 330; Venture capital finance; Liquidation preferences; Preferential claims; Option pricing